2010
DOI: 10.1186/1756-0500-3-37
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial findings in chronic granulomatous disease: report of twelve patients and review of the literature

Abstract: BackgroundChronic granulomatous disease is an extremely rare primary immunodeficiency syndrome that can be associated with various oral complications. This can affect high number of patients. However, data on oral complications is sparse. Here we will review the literature and describe the orofacial findings in 12 patients.FindingsThe age range was 5-31 years. Oral findings were variable, and reflected a low level of oral hygiene. They included periodontitis, rampant caries, gingivitis, aphthous-like ulcers, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 36 publications
0
15
0
3
Order By: Relevance
“…2,[16][17][18][19] However, Dar-Odeh et al reported presence of oral complications in 58% of their 12 CGD patients and biopsies of 2 showed chronic nonspecific mucositis. 20 Our patient presenting with the AR form of CGD had troublesome periodontal complaints and came to medical attention by the presence of chronic gingivitis, although he had a crowded history of serious infections. His serum IgE levels were high and he was referred to our unit with the probable diagnosis of HIES.…”
Section: Discussionmentioning
confidence: 97%
“…2,[16][17][18][19] However, Dar-Odeh et al reported presence of oral complications in 58% of their 12 CGD patients and biopsies of 2 showed chronic nonspecific mucositis. 20 Our patient presenting with the AR form of CGD had troublesome periodontal complaints and came to medical attention by the presence of chronic gingivitis, although he had a crowded history of serious infections. His serum IgE levels were high and he was referred to our unit with the probable diagnosis of HIES.…”
Section: Discussionmentioning
confidence: 97%
“…Fissured tongue has been seen more in individuals with Down syndrome than the general population. 57 Fissured tongue is a component of Melkerson-Rosenthal syndrome, characterized by the classic triad of facial palsy, facial swelling, and fissured tongue. 56,58-60 Fissured tongue is a benign condition and no specific treatment is indicated.…”
Section: Fissured Tonguementioning
confidence: 99%
“…La enfermedad granulomatosa crónica cursa con candidiasis, ulceraciones con pseudomembranas en cualquier parte de la mucosa oral, sinusitis recurrentes, linfadenitis cervicales, queilitis eccematosa, gingivitis intensa, lengua geográ fica, hipoplasia del esmalte, caries rampantes e infecciones cutá neas faciales 14,15 . Hay autores que la relacionan tambié n con la aparició n de periodontitis prepuberal generalizada 16 ; la periodontitis prepuberal se ha relacionado con una deficiencia en la adhesió n de los leucocitos 15 .…”
Section: Trastornos Funcionalesunclassified
“…Hay autores que la relacionan tambié n con la aparició n de periodontitis prepuberal generalizada 16 ; la periodontitis prepuberal se ha relacionado con una deficiencia en la adhesió n de los leucocitos 15 . Muchas de las manifestaciones se relacionan con factores gené ticos o sociales, como la falta de higiene oral, por lo que se recomienda un cuidado dental especializado y regular 14 .…”
Section: Trastornos Funcionalesunclassified